Benefits of Cost-Effectiveness of Remote Medical Care; Saudi Arabia paradigm - Alqudah, Hasan Salih Suliman (Journal of Economic, Administrative and Legal Sciences, 2021)
Previous and pieces studies of evidence showed that the remote medical care and the telemedicine tools not only facilitate access to healthcare services but also create cost saving for both the government and the patient. The research approach used in the study relies on theoretical approach by authenticated previous studies presented in this research the objective of this study will try to evaluate and analyze concerning studies to examine how telemedical applications can help patients to gain the expected healthcare anytime and anywhere, to reduce possible costs of traveling which seeking professional health care or searching for medical specific specialists. By addressing this situation in health sectors and to Saudi Arabia health care sector specifically. The study has concluded that the level of awareness of the different tools of telemedicine was somehow high, and most of the healthcare professionals have their own smart devices, and a high percentage of them were using those devices in their workplace s, as well as with their patients, also healthcare providers believe that telemedicine is very essential to healthcare systems, it is important to conduct further telemedicine training, workshops, conferences, courses, and many other tools should be provided to them to reach the maximum quality of healthcare, deep informative local studies should be done to assess the acceptability, some specialties had a great degree of acceptability to introduce the remote medical care tools, while other specialties have fewer degrees of acceptability so we should not waste our efforts on them.
Keywords: telemedicine; telehealth; Saudi Arabia; health care; Remote Medical Care; health care provider